Federación Cristiana de Campesinos salvadoreños (FECCA) y Unión de Trabajadores del Campo (UTC ): the making of the Salvadoran peasant movement revisited - Arriola Alarcón, Francisco Joel (2019)
In this paper, I review the process of making of the most important organizational structures (FECCAS and UTC) that sustained the radicalized cycle of unarmed peasant mobilizations deployed in El Salvador between 1969 and 1981, immediate years, these, to the civil war that faced militarily to the Frente Farabundo Martí para la Liberación Nacional (FMLN) and the Salvadoran State. The purpose of this task is to reconstruct the local process of making of the two largest popular organizations of the period, highlighting the way in which the emergence of both, although made possible by three large macro-processes of medium duration (decades), was the outcome of the situated and interactive action that a multiplicity of ingenious and creative actors (including the peasantry) deployed in the Salvadoran countryside during those years. For this paper, I have reviewed three sources of facts: the relatively abundant secondary literature of the period and object studied; the published memoirs of some of middle leaders of what was the peasant movement of that period; and internal and public documents of the FECCAS and UTC organizations.